Mission Groups and the New Politics of British Higher Education. (23rd January 2015) - Filippakou, Ourania; Tapper, Ted
Abstract This article explores the emergence and impact of the mission groups in British higher education. The central argument is that given the development of a mass and diversified model of higher education it was inevitable that the higher education institutions would form pressure groups, while increased marketisation and growing inter‐institutional competition have helped to sustain their presence. With particular reference to their input into the policy making process, it analyses how they contribute to a new politics of policy‐making and concludes by considering the future of the mission groups in the light of the recent demise of the 1994 Group.